The Relationship of Social Media Exposure and Willingness to Visit Siargao Island, Philippines: Destination Image as Mediator - Nicole Margareth Malibiran; Ken Ivan Myell T. Mallari; Maxine Hermione Mojica; Kate Anne D. Padua; Mark Nikko D. Pizarro; Jayvie O. Guballo (The Indonesian Institute of Science and Technology Research, 2026)
This study explored the relationship between social media exposure and willingness to visit Siargao Island, Philippines, with destination image serving as a mediating variable. It aimed to determine how online content about Siargao influences people’s perceptions and travel intentions through both cognitive and emotional responses. The researchers employed a quantitative correlational research design. Data were gathered from 300 active social media users aged 18 and above residing in Metro Manila who have seen Siargao content on any social media platform in the past 12 months. Data were collected using an online survey questionnaire and analyzed using frequency, percentage, weighted mean, Pearson correlation, and mediation analysis through regression and the Sobel test. Findings revealed strong positive correlations among the main variables: social media exposure and destination image, destination image and willingness to visit, and social media exposure and willingness to visit. Results also indicated that destination image partially mediates the effect of social media exposure on willingness to visit, suggesting that exposure to online content enhances people’s interest by creating a positive image of the island. The study concludes that social media plays a vital role in shaping tourists’ perceptions and travel decisions. Authentic, visually engaging, and experience-driven content about Siargao can strengthen destination image and influence potential visitors’ intentions, providing valuable insights for destination marketers and tourism stakeholders in promoting travel through digital platforms.